Proceedings of the 8th ACM SIGCOMM Conference on Internet Measurement 2008
DOI: 10.1145/1452520.1452542
|View full text |Cite
|
Sign up to set email alerts
|

Census and survey of the visible internet

Abstract: Prior measurement studies of the Internet have explored traffic and topology, but have largely ignored edge hosts. While the number of Internet hosts is very large, and many are hidden behind firewalls or in private address space, there is much to be learned from examining the population of visible hosts, those with public unicast addresses that respond to messages. In this paper we introduce two new approaches to explore the visible Internet. Applying statistical population sampling, we use censuses to walk t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
221
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(227 citation statements)
references
References 39 publications
4
221
1
Order By: Relevance
“…RELATED WORK 1) Large-scale Scanning: In 2008 Heidemann et al [35] started an Internet wide discovery scan of edge hosts. They were the first to census the IPv4 address space, but were limited to host discovery, not containing protocol or service specific results.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…RELATED WORK 1) Large-scale Scanning: In 2008 Heidemann et al [35] started an Internet wide discovery scan of edge hosts. They were the first to census the IPv4 address space, but were limited to host discovery, not containing protocol or service specific results.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…In [6], Heidemann et al presented a study of the active Internet over the period [2003][2004][2005][2006][2007][2008]. The presented census highlighted anomalies in the un-allocated address space and indicates the percentage of usage for allocated network blocks.…”
Section: Related Work and Backgroundmentioning
confidence: 99%
“…Active scans on the Internet are certainly an important source of information, as several studies have demonstrated that they can help reveal new kinds of vulnerabilities, monitor deployment of mitigation, and highlight hidden distributed ecosystems [5,6,7,8,11]. However, the IC results were published anonymously, and the methodology only partially described, which, as pointed out by the Cooperative Association for Internet Data Analysis (CAIDA) [1], leads to some important questions, such as: how does one know that the IC scan actually happened, and if it did, how does one know that the resulting data is correct?…”
Section: Introductionmentioning
confidence: 99%
“…aim to shed light on its structure [2], [13], user behavior [14], [17], host availability [6], [11], and web content [7], [10]; however, accurately capturing Internet-wide metrics has long remained a challenging research problem. The main tradeoff involves the amount of available hardware and the delay the user is willing to tolerate.…”
Section: Introductionmentioning
confidence: 99%
“…Sending such a large number of small packets presents a problem for Winsock and limits the duration of the measurement to days instead of minutes. A slightly different, but related, measurement goal that requires high pps sending rates is discovery of open services using horizontal scanning [1], [3], [6], [11], where each IP address in the IANA (3.3B destinations) or BGP (2.1B) space is probed with a packet on a given port. Instead of using months to scan the Internet as in prior work [1], [3], [6], [11], our goal in another ongoing project is to accomplish this activity in several hours/days.…”
Section: Introductionmentioning
confidence: 99%